Development of microstructure of steel for thermal power generation - Kvackaj, Tibor (Materiali in tehnologije, 2007)
The evolution of microstructure during the reheating and cooling of steel for thermal power generation was investigated. On the basis of the microstructure produced during cooling a CCT diagram is proposed
Keywords: martenzitna jekla; feritno jeklo; turbine; mikrostruktura